An uncovered interest parity condition that worked - The continental investment demand for London bills of exchange during the gold standard (1880 -1914) - Nils Herger (Swiss National Bank, Study Center Gerzensee, 2015)
This paper examines an uncovered interest parity (UIP) condition that arguably held as regards the continental investment demand for London bills of exchange during the classical gold standard. At that time, practical guide books about the foreign exchanges explained in detail how exchange and interest rates were connected. For data covering the 1880 to 1914 period, modern econometric methods uncover indeed that the interest from discounting bills of exchange in the open money markets of Paris, Amsterdam, and to a large degree also Berlin, and the return from investing in London bills followed the postulated proportional relationship. This result is remarkable given the widespread rejection of the UIP with modern data.
Keywords: F31; N13; N23; 330; Exchange rates; Gold standard; Uncovered interest parity condition; Uncovered interest parity puzzle